The effect of the NSPIxD model’s integration on knowledge, perceived awareness, and perceived motivation through mobile learning / Arifah Fasha Rosmani, Ariffin Abdul Mutalib and Siti Mahfuzah Sarif - Rosmani, Arifah Fasha; Abdul Mutalib, Ariffin; Sarif, Siti Mahfuzah (UiTM Cawangan Perlis, 2024)
Tablets, smartphones, and wearable devices can be beneficial in promoting academic learning and have evolved into the primary teaching method in formal and informal education. Concurrently, multimedia components can boost user engagement and interest in mobile applications and increase users' usage and attention to them. Celebrating the trend, a study on Islamic mobile applications integrated with the Signaling principle and Nielsen's Design Guideline investigates the knowledge and perceived awareness of the target users' context and perceived motivation in using the learning material. This research is inspired to intensify the Islamic mobile app user's motivation to use the app, uplift their interest, and increase their awareness and knowledge of Islamic content, particularly in Asmaul Husna. Islamic mobile apps are suggested to employ the Signaling principle since these principles guide attention, organization, knowledge integration, and reduce extraneous load. The research is divided into three stages comprised of theoretical study, development, and evaluation. The study generally finds that students' knowledge and perceived awareness of Asmaul Husna was increased by Asmaul Husna Mobile Application (AHMA) for both presentation modes which are AHMA-0 (not integrated with NSPIxD Model) and AHMA-NSPIxD (integrated with NSPIxD model). It demonstrates AHMA's efficacy as an alternative and creative approach to expanding the knowledge and perceived awareness of Asmaul Husna among students and their perceived motivation for the learning materials. The study sample is restricted to undergraduate students between 18 and 24. Therefore, this study suggests that future studies should also be extended to other learners' levels and a broader spectrum